2016
DOI: 10.1017/s0033291716000532
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of pre-trauma risk factors for post-traumatic stress disorder and depression

Abstract: BackgroundIt is unclear which potentially modifiable risk factors best predict post-trauma psychiatric disorders. We aimed to identify pre-trauma risk factors for post-traumatic stress disorder (PTSD) or major depression (MD) that could be targeted with resilience interventions.MethodNewly recruited paramedics (n = 453) were assessed for history of mental disorders with structured clinical interviews within the first week of their paramedic training and completed self-report measures to assess hypothesized pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
163
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(178 citation statements)
references
References 43 publications
10
163
2
3
Order By: Relevance
“…Whereas other studies have shown depressive attribution style to be positively correlated with PTSD symptom severity (e.g. Kleim et al, 2011;Wild et al, 2016), this is the first study to highlight the crucial role of these depressive attributions in the relationships between PMIEs and PTSD. Thus, these findings may ultimately lead researchers to identify a possible intervention point, as will be discussed below.…”
Section: Discussioncontrasting
confidence: 67%
“…Whereas other studies have shown depressive attribution style to be positively correlated with PTSD symptom severity (e.g. Kleim et al, 2011;Wild et al, 2016), this is the first study to highlight the crucial role of these depressive attributions in the relationships between PMIEs and PTSD. Thus, these findings may ultimately lead researchers to identify a possible intervention point, as will be discussed below.…”
Section: Discussioncontrasting
confidence: 67%
“…However, these response rates compare favourably to those achieved in other large-scale prospective college student surveys (39-44%) (Eisenberg et al, 2013;Paul, Tsypes, Eidlitz, Ernhout, & Whitlock, 2015). In addition, (Berking, Wirtz, Svaldi, & Hofmann, 2014;Cole & Dendukuri, 2003;Ebert, Hopfinger, & Berking, 2017;Korten, Comijs, Lamers, & Penninx, 2012;Pelkonen, Marttunen, Kaprio, Huurre, & Aro, 2008;Wild et al, 2016). As a result, the strength of the composite risk index found here should be considered a lower bound estimate compared to the estimate that might be obtained in future research that includes additional predictors.…”
Section: Limitationssupporting
confidence: 67%
“…According to our model, our main mediator of the association between transgressive acts of betrayal and PTSD symptoms was depressive attributions. Other studies have already shown that depressive attribution style correlated with PTSD symptom severity (e.g., Kleim et al., ; Wild et al., ). However, this is the first study to highlight the crucial role of these depressive attributions in the creation of PTSS following PMIEs, and may give us a lead to a possible intervention point.…”
Section: Discussionmentioning
confidence: 88%
“…Both cross‐sectional and longitudinal studies have pointed out that this pessimistic attributional style might be a cognitive risk factor that predicts depressive reactions and chronic depression (e.g., Wiersma et al., ). Given the strong comorbidity between PTSD and depression (Ginsburg, Ein‐Dor & Solomon, ), it is not surprising that the depressive attribution style also correlated with PTSD (e.g., Kleim, Gonzalo, & Ehlers, ; Wild, Smith, Thompson, Béar, Lommen, & Ehlers, ), number and distress of traumatic experiences, and posttraumatic cognitions (Désirée et al., 2012).…”
Section: Introductionmentioning
confidence: 99%